Attenuation and De-focusing During High-Intensity Focused Ultrasound Therapy Through Peri-nephric Fat - Ritchie, R; Collin, J; Coussios, C; Leslie, T (2013)
High-intensity focused ultrasound (HIFU) is an attractive therapy for kidney cancer, but its efficacy can be limited by heat deposition in the pre-focal tissues, notably in fat around the kidney (peri-nephric fat), the acoustic properties of which have not been well characterized. Measurements of attenuation were made using a modified insertion-loss technique on fresh, unfixed peri-nephric fat obtained from patients undergoing kidney surgery for cancer. The de-focusing effect of changing the position of the fat layers was also investigated using fresh subcutaneous fat from euthanized pigs. The mean attenuation of human peri-nephric fat was found to be 11.9 ± 0.9 Np/m (n= 10) at 0.8 MHz, the frequency typically used for HIFU ablation of kidney tumors, with a frequency dependence of f1.2. A typical 2- to 4-cm thickness of peri-nephric fat would result in a de-rated intensity of 3%-62% at 0.8 MHz compared with a hypothetical patient with no peri-nephric fat. Through the use of freshly excised porcine subcutaneous fat, the presence of fat 100 mm in front of the focus was found to have a de-focusing effect of approximately 1 mm in both transverse directions, which corresponds to a full HIFU beam width off-target. Peri-nephric fat may significantly affect both the intensity and accuracy of HIFU fields used for the ablation of kidney cancer. © 2013 World Federation for Ultrasound in Medicine and Biology.